Pendampingan Pembelajaran Ibadah Amaliyah Siswa SDN 2 Wates Kecamatan Slahung Ponorogo - Tifani, M. Akhlis Azamuddin; Kholilullah, Abdul Aziz; Wuran, Affan Mahatma; Zarkasyi, Azmi; Gunawan, Sahrul; Abdillah, Rizali; Kamil, Achmad Fauzan; Prayogi, Dwiki Agung; Yanuaryogi, Muhammad; Sasongko, Yogi Banar (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Learning religious practices is an important part of Islamic religious education that functions to shape students' religious character from an early age. However, its implementation in elementary schools still faces various obstacles, such as low student understanding, lack of teacher guidance, and less interesting learning methods. This community service program was implemented at SDN 2 Wates by nine students of Darussalam Gontor University from various study programs with the aim of improving students' understanding and skills in practicing religious practices. The activity method includes three stages, namely: (1) preparation through partner coordination, preparation of pre-tests, and teaching materials; (2) implementation with a participatory approach and direct practice adjusted to student competencies; and (3) evaluation through observation, questionnaires, and post-tests. The results of the program showed an increase in students' understanding of the procedures for worship and a growing awareness of the importance of worship in everyday life. This activity shows that an interactive and collaborative approach is effective in improving the quality of learning religious practices at the elementary level.